Investigation of multilayer planar hybrid plasmonic waveguide and bends. Issue 9 (4th April 2016) - Sharma, P.; Kumar, V.D.
Abstract : Hybrid metal insulator metal plasmonic waveguide has been investigated at 1550 nm wavelength using frequency‐domain electromagnetic solver of computer simulation technology microwave studio. This waveguide overcomes the limitations of conventional plasmonic metal insulator metal waveguide and provides good balance between propagation length and confinement. Propagation length up to 2.5 mm and confinement factor more than 80% have been observed. Waveguide bends such as 90° and S‐shaped, based on the presented waveguide have been examined; these bends exhibit more than 90% transmission efficiency in a confinement area of 40 × 200 nm 2 . The application of these structures in the design of chip scale integrated circuitry is motivated.